Empowering Marginalised Women in Remote Indian Villages: An Impact Study - Saikia, Udoy; Chalmers, Jim; Michael, Dency; Orrell, Janice (Routledge Contemporary South Asia Series, 2025)
Saikia, Chalmers, Michael and Orrell explore the impact of social education on gender inequalities in rural Tamil Nadu where highland women’s lives are damaged by discrimination, marginalisation and deprivation. Social education refers to agent-oriented learning experiences focused on power relations designed to help oppressed people regain their humanity in the struggle for empowerment. The book begins with the recognition that wellbeing is dependent on access to opportunities given that gender parity in tertiary education has not transferred to good jobs. This implies education is a necessary but insufficient indicator of wellbeing in the absence of empowerment. Hence, it investigates interconnections between empowerment (self-efficacy, social action and human rights) and multiple dimensions of wellbeing (living standards/ livelihoods, physical and mental health, and education). It articulates how such hopes and expectations are empirically founded, thereby presenting some of the answers that readers need to move from grievance to a future that is more conducive to friendships and mutuality. A vital resource for scholars, students, researchers and professionals interested in development studies, human rights (law and social science), anthropology of development, gender in development, public health administration, governance/ public administration, and welfare economics.